INSTITUTIONAL FRAMEWORK FOR SME TRANSFORMATION IN THE CONTEXT OF DIGITALISATION (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article examines institutional mechanisms for ensuring the structural transformation of small and medium-sized enterprises in the trade and services sector under the conditions of economic digitalization. The role of digital technologies in the transformation of the entrepreneurial sector is substantiated, and the key directions for modernizing the institutional environment for the development of small and medium-sized enterprises are identified. The impact of digitalization on structural changes in the trade and services sector is analyzed, in particular the development of e-commerce, digital platforms, online services, and platform-based business models.The study systematizes the key institutional barriers to the development of small and medium-sized enterprises in Ukraine and conducts a comparative analysis of European practices supporting the digital transformation of the entrepreneurial sector. It is proved that the effectiveness of structural and institutional transformation largely depends on the quality of the regulatory environment, the level of digital infrastructure development, the availability of financial resources, digital competencies, and the adaptability of public policy.A conceptual model of institutional support for the structural transformation of the small and medium-sized enterprise sector under the conditions of economic digitalization is proposed, and directions for improving public support mechanisms for entrepreneurship in accordance with European practices are substantiated.
Keywords: small and medium-sized enterprises; structural and institutional transformation; economic digitalization; digital transformation; institutional environment; public policy; European practices